Feeding, stooling and sleeping patterns in infants with colic - a randomized controlled trial of minimal acupuncture - Hallström Inger; Kvorning Nina; Landgren Kajsa (BMC, 2011)
Abstract Background The aim was to describe the feeding- and stooling patterns of infants with colic and evaluate the influence of minimal acupuncture. Methods A prospective, randomized, controlled, blind clinical study was conducted at a private acupuncture clinic in Sweden. 90 otherwise healthy 2-8 weeks old infants, born after gestational week 36, fulfilling the criteria for infantile colic and not medicated with dicyclomine, were included. 81 infants went through a structured program consisting of six visits to the clinic, twice weekly. Infants randomized to receive acupuncture were given minimal, standardized acupuncture for two seconds in LI4. Frequency and size of stooling, as well as duration of, and intervals between, feeding sessions were reported by parents in a diary. Parental assessment of sleep and comments on stooling and side effects were collected in a questionnaire. Results At baseline when the mean age was five weeks, infants in both groups were fed a median of eight times/day, 148 min/day, with considerable variations. No differences were found between groups in the frequency and duration of feeding during the intervention weeks. Furthermore there were no significant differences between the groups regarding the frequency of stooling, neither at baseline, at which point the infants of both groups had bowel movements 4.2 times/day, nor during the intervention weeks. There was an expected decrease in frequency of stooling in both groups, reaching 2.1 (p = 0,001) in the acupuncture group and 3.1 (p < 0,001) in the control group. The groups differed regarding large bowel movements which decreased linearly in the control group (p = 0,011) but not in the acupuncture group (p = 0,787). More parents in the acupuncture group than in the control group (28% and 15% respectively, p = 0.006) experienced the infant's sleep to be "better" or "much better." No other significant differences were found. However, parents described a normalized stooling and experienced an improvement in colic in their infants more frequently in the acupuncture group than in the control group. Conclusions Infants with colic in the present study had a higher frequency of stooling than reported internationally in healthy infants. Minimal acupuncture had no major effect on feeding, stooling and sleep, although a minor effect of minimal acupuncture on stooling and sleep cannot be ruled out. Trial registration ClinicalTrials.govID NCT00860301